SAT0493 Medial Meniscal Damage and Extrusion Increase Risk of Incident Radiographic Osteoarthritis. (23rd January 2014) - Guermazi, A.; Kwoh, C. K.; Hannon, M. J.; Hunter, D. J.; Boudreau, R.; Eckstein, F.; Grago, J.; Wang, Z.; Roemer, F. W.
Abstract : Background: Radiography is only able to depict structural joint damage at advanced stages of knee osteoarthritis (OA). Pre-radiographic structural damage to the joint is likely to increase the risk of incident radiographic OA (ROA). The menisci are crucial for preservation of joint integrity and meniscal damage alters joint biomechanics, potentially leading to greater peak stress and a more rapid onset of ROA. Objectives: The aim of the study was to assess if presence and severity of meniscal damage and extrusion one year prior to the occurrence of incident ROA (timepoint "P-1") increases the risk for incident ROA in a nested, matched case-control study in the Osteoarthritis Initiative (OAI) cohort. Methods: Participants were drawn from the OAI including 4796 participants with, or at risk of knee OA. We studied 105 knees that developed incident ROA before the 48 month visit. Knees were selected based on the following definition: either KL 0 in both knees or KL1 in both knees or KL 0 in one knee and KL 1 in the contralateral knee at baseline. They were matched with a control knee that did not develop incident ROA, with the same KL grade in both knees at baseline, and for gender and age within 5 years. MR images were acquired at four OAI clinical centers using Siemens Trio 3 T scanners. MRIs were read for medial (m) and lateral (l) meniscal morphology in the m/l anterior horn, m/l body, m/l posterior horn using the semiquantitative MOAKS system. In MOAKS, grade 0 depicts a normal meniscus and grade 1 intrameniscal signal changes, grades 2-5 code different types of meniscal tears while grades 6-8 code different grades of meniscal maceration. Extrusion was scored on coronal images from 0-3. Conditional logistic regression was used to assess the risk of incident ROA based on the extent of meniscal damage and extrusion one year prior to the case defining visit (i.e. at P-1). Results: Subjects were on average 58.8 years old (SD ± 8.6), predominantly female (62.9%) and overweight (mean BMI 27.9 SD ± 4.6). Risk of incident ROA was significantly increased for knees exhibiting any pathology of the medial meniscal body at P-1 (OR=2.5 95% confidence interval [CI] [1.28, 4.88]) or anterior lateral horn (OR = 6.67 95% CI[1.98, 22.43]) when compared to the knees with normal meniscal morphology in that region as the reference. Knees with a maximum MOAKS grade of ≥2 in any of the 3 locations of the medial compartment had an increased risk for incident ROA (OR= 4.27, 95% CI [1.66, 10.98]). Knees with any medial extrusion had an increased risk of ROA incidence when compared to knees without medial extrusion (OR=2.77 95% CI [1.47, 5.22]. Conclusions: Any pathology of the medial meniscal body or the lateral anterior horn predicted incident ROA one year later. A maximum grade of 2 or more medially predicted incident ROA compared to knees with a maximum grade of 0 or 1. In addition, any medial extrusion increased risk for ROA. Disclosure of Interest: A. Guermazi Shareholder of: Boston Imaging Core Lab, LLC, Consultant for: Astra Zeneca, Genzyme, Novartis, Stryker, Merck Serono, C. K. Kwoh: None Declared, M. Hannon: None Declared, D. Hunter Grant/research support from: Australia Research Council Future Fellowship, Consultant for: DonJoy, NIH, Stryker, R. Boudreau: None Declared, F. Eckstein Shareholder of: Chondrometrics, J. Grago: None Declared, Z. Wang: None Declared, F. Roemer: None Declared